2020
DOI: 10.3390/ijms21165882
|View full text |Cite
|
Sign up to set email alerts
|

From Ivacaftor to Triple Combination: A Systematic Review of Efficacy and Safety of CFTR Modulators in People with Cystic Fibrosis

Abstract: Over the last years CFTR (cystic fibrosis transmembrane conductance regulator) modulators have shown the ability to improve relevant clinical outcomes in patients with cystic fibrosis (CF). This review aims at a systematic research of the current evidence on efficacy and tolerability of CFTR modulators for different genetic subsets of patients with CF. Two investigators independently performed the search on PubMed and included phase 2 and 3 clinical trials published in the study period 1 January 2005–31 Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 45 publications
2
68
0
Order By: Relevance
“…Of the four CFTR modulators, LUM/IVA was seemingly associated with a higher frequency of AE, respiratory-related AE in particular. While this observation may be due to real-world studies predominantly reporting on experience with LUM/IVA, it reflects what has also been observed in the clinical trial setting [ 7 , 94 , 95 ]. Dyspnea and chest tightness with LUM/IVA appear to have occurred more often in real-world studies, with higher frequencies overall and of discontinuation than reported in clinical trials.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Of the four CFTR modulators, LUM/IVA was seemingly associated with a higher frequency of AE, respiratory-related AE in particular. While this observation may be due to real-world studies predominantly reporting on experience with LUM/IVA, it reflects what has also been observed in the clinical trial setting [ 7 , 94 , 95 ]. Dyspnea and chest tightness with LUM/IVA appear to have occurred more often in real-world studies, with higher frequencies overall and of discontinuation than reported in clinical trials.…”
Section: Discussionmentioning
confidence: 54%
“…When interpreting the real-world AE findings in the context of clinical trial data, it is prudent to keep in mind that study populations in clinical trials are fundamentally different from real-world populations due to reasons such as strict inclusion/exclusion criteria and participants being inherently more motivated to continue with the assigned therapy [ 93 ]. In clinical trials evaluating CFTR modulators, study participants were clinically stable and those with severe or minimal lung disease (i.e., ppFEV 1 < 40% and > 90%, respectively) were typically excluded or grossly underrepresented [ 94 , 95 ]. Another important consideration is the differences between observational studies and clinical trials in AE evaluation and reporting.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, depression, anxiety, sleep paralysis with hypnopompic hallucinations [16] and testicular pain [17] have been reported after initiation of Trikafta therapy. Another common adverse event reported in patients treated with CFTR modulators is an abnormal liver function that is however moderate in severity and did not require drug discontinuation [18].…”
Section: Introductionmentioning
confidence: 99%
“…Change of treatment paradigm started in 2012, with the availability of the first therapy targeting the CFTR protein basic defect on a small minority of the population carrying at least one gating mutation 10,11 . This new class of drugs called CFTR modulators (CFTRm) rapidly increased with the addition of new combinations targeting additional CF patient groups, ivacaftor/lumacaftor, ivacaftor/tezacaftor and more recently ivacaftor/tezacaftor/elexacaftor, each of them approved for use in patients with specific genotypes 12 . Although genotype does not fully correlate with phenotype, patients homozygous forF508del , the most frequently represented mutation worldwide, generally have a rapidly progressive disease while patients with mutations associated with residual function of the CFTR protein tend to have a slower course of disease 13 .…”
Section: Introductionmentioning
confidence: 99%